MEMAHAMI HUBUNGAN KEAKRABAN ORANG TUA DENGAN ANAK YANG TINGGAL DI PESANTREN - Nur Mustika, Ratu; Noor Rakhmad, Wiwid (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
Pesantren or Islamic Boarding School is one of education alternative institution for children. Based on regulations that is applied in Pesantren as general, children are required to live there without any contact from outside pesantren and also not allowed to use communication technology. Change in communication experienced by parents and children can cause consequences for the relationship between both of them. This research aims to describe the experiences of parents and children living in Islamic boarding schools in maintaining intimate relationships. The method used in this study is descriptive qualitative with interpretive paradigm and phenomenological approach. The theories used include Relational Dialects Theory, Relationship Maintenance Theory and Family Relationship Scheme Theory. Data in this research is collected through in depth interviews to three pairs of parents and children from different pesantren. The research showed that parents and children maintain relationship by maintaining communication via telephone provided by pesantren and commiting face to face meeting during parents-child visit. Parents and children share news and feelings each other regularly to maximize parents-child interaction time. Children ever experienced upleasant feeling whaen they are far away from parents and tried to run away with several plans made. Parents do not just let kids alone but also keep an eye on their children by maintaining communication with each other and asking how their condition in Pesantren. Parents constantly provide support, advice and attention so their children feel cared and motivated in their education. In addition, famalies open up each other by conveying news, feelings and their development of the latest activities carried out by each member. Parents and children also commit acts of affection by expressing directly, kissing, hugging and expressing love in their own way to maintain relationship between parents and children.